Dynamic response of Advanced Placed Ply composites. (1st January 2023) - Kok, Rutger; Peroni, Marco; Martinez-Hergueta, Francisca; Pellegrino, Antonio
Abstract: This work investigates the high strain rate behavior of AP-PLY composites. The large representative volume elements and brittle nature of this material necessitated the use of a bespoke Split-Hopkinson bar apparatus. AP-PLY and baseline laminates were subjected to tensile loading at strain rates of 30 s −1 . Results were compared with quasi-static data to evaluate whether the laminate architecture introduced any strain rate dependency. In addition, the dynamic experiments were simulated using a multiscale modeling framework, providing further insights into the micromechanisms governing material behavior. The moduli of the AP-PLY composites were found to be strain rate independent, however, strengths were found to be marginally higher than those of their baseline counterparts. At high strain rates, the strain concentrations induced by the geometry of the individual tapes at through thickness undulations and tow boundaries were less significant due to reduced out-of-plane tow straightening and delamination. As a result, no reduction in AP-PLY strength in comparison to the baseline laminates was obtained. These differences in deformation micromechanisms led to an improvement of the damage tolerance when subjected to dynamic loading. Graphical abstract: Highlights: The tensile response at high strain rates of AP-PLY laminates is investigated for the first time. The experimental campaign is conducted at the world's largest Split Hopkinson Bar. Further insight into the failure mechanisms is provided by multiscale numerical simulations. AP-PLY preforming improves stiffness and strength when subjected to high strain rates.